Zwei Alpentäler im Klimawandel - Auer, Ingeborg (alpine space - man and environment, 2010)
The history of climate change in the valleys near Rauris and Flattach north and south of the Hohe Tauern mountain ridge was investigated in the project "A Tale of Two Valleys". The story begins long before human settlement and projects into the future. Increasing impact of human activity causes a growing responsibility for the climate on earth. Concurrently precautions are required to cope with the adverse effects of climate change. Change is a fact. Understanding interactions between climate, landscape, and economy is pivotal to meet the challenge.